Pengaruh Media Audio-Visual terhadap Kecerdasan Spiritual - Nailul Authar (Aṭfāluna: Journal of Islamic Early Childhood Education, 2018)
This research aims to determine the influence of audio-visual media on the intelligence of children worship in the TK Pembina Kecamatan Idi Rayeuk. This type of research is class action research (PTK), conducted in July 2018 to August 2018. This research consists of two cycles with four main activities that exist on each cycle, namely planning, observation action, Reflaksi. Data is analyized using qualitative data and quantitative data. The subject in this study was a child in TK Pembina. The data collection techniques used are oral test and observation techniques.